(untitled) (Herald of the National Children’s Medical Center, 2025)
Aim. To develop and validate TIP-M modification for distal hypospadias repair. Materials and methods. Prospective cohort study of 56 patients (mean age 6.4±3.8 years) with distal hypospadias treated using TIP-M technique. The modification involves limiting urethral plate incision depth to 2mm with defect replacement using vascularized flap from inner prepuce. Results. Early complications occurred in 26.8% patients, late complications in 7.1%. Excellent overall results achieved in 73.2% cases. Normal voiding restored in 100% patients with excellent cosmetic outcomes in 94.6%. Reoperation rate was 5.4%. Mean urethral plate width increase was 35.2±8.7%. Conclusion. TIP-M modification demonstrates superior outcomes compared to classical techniques, providing universal applicability regardless of anatomical conditions. The technique can be recommended as first-choice method for distal hypospadias repair.